Biopolymer production from biomass produced by Nordic microalgae grown in wastewater. (May 2023) - Mehariya, Sanjeet; Plöhn, Martin; Jablonski, Piotr; Stagge, Stefan; Jönsson, Leif J.; Funk, Christiane
Graphical abstract: Highlights: Biomass of Nordic microalgae was used as feed for bacterial biopolymer production. Thermochemical pre-treatment with 1% H2 SO4 improved the solubilization of total sugars. Maximal PHB content (27% of DW) was achieved with hydrolysate of Chlorococcum sp. Nordic microalgae can combine wastewater reclamation with PHB production. Abstract: Biomass from four different Nordic microalgal species, grown in BG-11 medium or synthetic wastewater (SWW), was explored as inexpensive carbohydrate-rich feedstock for polyhydroxybutyrate (PHB) production via microbial fermentation. Thermochemical pre-treatment (acid treatment followed by autoclavation) with 2% hydrochloric acid or 1% sulphuric acid (v/v) was used to maximize sugar yield prior to fermentation. Pre-treatment resulted in ∼5-fold higher sugar yield compared to the control. The sugar-rich hydrolysate was used as carbon source for the PHB-producing extremophilic bacterium Halomonas halophila . Maximal PHB production was achieved with hydrolysate of Chlorococcum sp. (MC-1) grown on BG-11 medium (0.27 ± 0.05 g PHB/ g DW), followed by hydrolysate derived from Desmodesmus sp. (RUC-2) grown on SWW (0.24 ± 0.05 g PHB/ g DW). Nordic microalgal biomass grown on wastewater therefore can be used as cheap feedstock for sustainable bioplastic production. This research highlights the potential of Nordic microalgae to develop a biobased economy.